2003
DOI: 10.1007/s11664-003-0242-8
|View full text |Cite
|
Sign up to set email alerts
|

Wetting interaction between Sn-Zn-Ag solders and Cu

Abstract: The wetting interaction of Sn-(7.1-9)Zn-(0-3)Ag solders with Cu was investigated from 230°C to 300°C. The wetting time, wetting forces, and activation energy of the wetting reaction were studied. The wetting time decreases with increasing temperature and increases with Ag content. The wetting force exhibits a disproportional correlation to temperature rise, while no trend was observed with respect to Ag content. The wetting behavior was ascribed to the interaction between Cu and Zn. The AgZn 3 compound was for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Since Zn has a strong chemical affinity with the alloying element, it reduces the soluble Zn content of solders. Therefore, the effects of adding other elements, such as Cu, Ag or Co, into the SneZn solders on the formation of intermetallic compounds (IMC) at the interfaces were extensively investigated [12,13,17,18]. However, only a few studies associated with Ni 5 Zn 21 growth kinetics have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since Zn has a strong chemical affinity with the alloying element, it reduces the soluble Zn content of solders. Therefore, the effects of adding other elements, such as Cu, Ag or Co, into the SneZn solders on the formation of intermetallic compounds (IMC) at the interfaces were extensively investigated [12,13,17,18]. However, only a few studies associated with Ni 5 Zn 21 growth kinetics have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth, indium and antimony are the most popular metals among the modifiers of soldering properties of the Sn-Zn eutectic. [1][2][3][4][5] However, the main interest of numerous research teams has so far concentrated on the measurements of many technological properties neglecting at the same time unquestionably difficult thermodynamic examinations. Hence, the experimental results of activities of components for many ternary alloys including the Sb-Sn-Zn ones are scarcely found in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tendency of oxidation, and poor wetting ability of this alloy system confine its application [5,6]. In recent years, to overcome the shortfall of Sn-9Zn, some authors have tried to add a third element, such as In [7], Bi [8][9][10], Al [11][12][13][14][15], Ag [16][17][18], and Ce/La [19][20][21] to the Sn-Zn binary system to improve the melting temperature, wettability, oxidation resistance, corrosion, and mechanical properties of the alloy.…”
Section: Introductionmentioning
confidence: 99%